Tracing the trajectory of behavioral impairments and oxidative stress in an animal model of neonatal inflammation. (9th July 2015) - MacRae, M.; Macrina, T.; Khoury, A.; Migliore, M.M.; Kentner, A.C.
Highlights: Neonatal inflammation led to time-dependent affective and cognitive disruptions. Social behavior was reduced in neonatal (n)LPS-treated juvenile rats. Prefrontal glutathione was reduced in nLPS-treated juvenile male rats. Spatial memory was intact in juvenile male nLPS rats but was impaired in adults. Enrichment rescued nLPS-induced reductions in social interaction and glutathione. Abstract: Exposure to early-life inflammation results in time-of-challenge-dependent changes in both brain and behavior. The consequences of this neural and behavioral reprogramming are most often reported in adulthood. However, the trajectory for the expression of these various changes is not well delineated, particularly between the juvenile and adult phases of development. Moreover, interventions to protect against these neurodevelopmental disruptions are rarely evaluated. Here, female Sprague–Dawley rats were housed in either environmental enrichment (EE) or standard care (SC) and their male and female offspring were administered 50 μg/kg i.p. of lipopolysaccharide (LPS) or pyrogen-free saline in a dual-administration neonatal protocol. All animals maintained their respective housing assignments from breeding until the end of the study. LPS exposure on postnatal days (P) 3 and 5 of life resulted in differential expression of emotional and cognitive disruptions and evidence of oxidative stress across development. Specifically, social behavior was reduced in neonatal-treated (n)LPS animals at adolescence (P40), but not adulthood (P70). In contrast, male nLPS rats exhibited intact spatial memory as adolescents which was impaired in later life. Moreover, these males had decreased prefrontal cortex levels of glutathione at P40, which was normalized in adult animals. Notably, EE appeared to offer some protection against the consequences of inflammation on juvenile social behavior and fully prevented reduced glutathione levels in the juvenile prefrontal cortex. Combined, these time-dependent effects provide evidence that early-life inflammation interacts with other developmental variables, specifically puberty and EE, in the expression (and prevention) of select behavioral and molecular programs.